Geotechnical rank in the The Playón, Mapasingue and The Pista sectors, Nambija Mining District - Andrade Mantilla, Fernanda Dayana (2023)
The research is based geomechanical qualification of rock mass, in the underground mining works of the Asonambile Concession (Nambija Mining District), through the Bieniawski’s RMR system (1989) and the Barton’s Q index (2000) in addition to the empirical correlations to determine the Hoek’s GSI index (2002), which allowed defining the geomechanical parameters and with it, the behavior and geotechnical quality of 2,473 linear meters of underground galleries. The geomechanical parameters indicate that mining works located up to 50 m deep from the surface, present a minimal risk of rock bursting; while those located from 100 m, present violent rock bursting, causing instability. Geotechnical tests "in situ" and laboratory, carried out between 2010 and 2014 by the Instituto Nacional de Investigación Geológico, Minero y Metalúrgico (current Instituto de Investigación Geológico y Energético), as part of several projects in the Nambija Mining District, have been considered for extrapolation and comparison with the geomechanical evaluations of this research; in addition to allowing the calibration of a geological model of sector.Besides, the present study foresees an empirical support system based on the Barton’s Q.